The Relationship Of Knowledge And Social Culture To The Success Of Exclusive Breast Feeding In Kuprik Health Center - Lamtiar Manurung; Nining Istighosah; Riza Tsalatsatul Mufida; Nita Dwi Astikasari (Journal of Health Science Community, 2024)
One way to prevent infant mortality is exclusive breastfeeding without additional food. A preliminary study at the Kuprik Community Health Center in 2023, of 20 breastfeeding mothers, only 14 (70%) were implementing exclusive breastfeeding and 6 (30%) weren’t implementing exclusive breastfeeding. To determine the relationship between knowledge and socio-culture on the success exclusive breastfeeding in the Kuprik Community Health Center working area.The research was conducted on 11 December 2023-12 January 2024 in the working area of Kuprik Community Health Center. The research uses an analytical observational research design with a retrospective approach. With the stratified random sampling technique, a sample of 63 was obtained. The Chi-Square test was used to determine relationship between two variables.The research results showed that 43 (68.3%) respondents had poor knowledge about exclusive breastfeeding, 35 (55.6%) had poor social culture regarding exclusive breastfeeding, and 39 (61%) didn’t give exclusive breastfeeding to their babies. .9%). Chi-Square analysis found that there was a relationship between knowledge and exclusive breastfeeding, p value = 0.000 < 0.05, and there was a socio-cultural relationship with exclusive breastfeeding, p value = 0.001 < 0.05. There is a relationship between knowledge and social culture towards exclusive breastfeeding. It is hoped that midwives will provide accurate and comprehensive counseling about exclusive breastfeeding, especially its benefits, so that mothers can understand it and can change a bad culture into a good culture for the sake of the baby's health.